ANALISIS STRATEGI PEMASARAN DALAM MENINGKATKAN PENJUALAN PADA WISATA KULINER DI KECAMATAN MUARA TEWEH KABUPATEN BARITO UTARA - Liawati - (Sekolah Tinggi Ilmu Ekonomi Muara Teweh, 2025)
Haris Munadi, Management, 2022, Marketing Strategy Analysis in increasing sales in Culinary Tourism in Wisata Villag This study aims to find out and analyze how the marketing strategy for Culinary Tourism in Wisata Village, South Kalimantan province, is known that there are several problems The type of research in this research is descriptive qualitative, the data analysis techniques used are interviews, observation and documentation. village, Culinary Tourism in Wisata Village, South Kalimantan province. The results of this study are that it is known that Culinary Tourism in Wisata Village, South Kalimantan province does not use the proper marketing strategy, and it is hoped that Culinary Tourism in Wisata Village, South Kalimantan province can use the proper marketing strategy, namely 7P so that it can increase sales of Culinary Tourism in Wisata Village, South Kalimantan Province.